The use of audio-visual aids in recalling plot and characters in Step by Wicked Step / Yegnese Raja - Yegnese, Raja (2017)
This research was carried out to identify the challenges faced by learners in recalling plot and characters in Step by Wicked Step and how they address these challenges. This research also looks into the extent audio-visuals aids (AVA) assist in the recalling of the plot and the characters in the novel. This research is also to identify learners’ attitude towards the use of AVA in the recalling of the plot and the characters of the said novel. Quantitative analysis was used to measure the difference AVA makes in learners’ ability to recall plot and characters. The sample for this study was eighty Form 5 students from a school in a rural area of Melaka. They were assigned into two groups; the controlled group and the experimental group. The experimental group was given the treatment which was the AVA while the controlled group had a traditional-method lesson. Focus-group discussion was also carried out with ten participants from each group. The quantitative findings of the study indicated that AVA do help participants to recall the plot and the characters better though not very significantly. However, participants gave positive response towards the use of AVA in English Literature lessons. The data revealed that participants faced numerous challenges to recall the plot and characters of the novel. One of the main challenges is their inability to remember all the characters in the novel.